Tobacco Road - Ford, John, 1894-1973; Zanuck, Darryl Francis, 1902-1979; Johnson, Nunnally; Grapewin, Charles, 1869-1956; Rambeau, Marjorie, 1889-1970; Tierney, Gene; Tracey, William, 1917-1967; Patterson, Elizabeth, 1875-1966; Andrews, Dana, 1909-1992; Summerville, Slim, 1892-1946; Bond, Ward, 1903-1960; Mitchell, Grant, 1874-1957; et al. (Ford at Fox collection., 2007)
Bankers plot to take over the farm of shiftless Jeeter Lester and his family.